Creating oppotunities for STT ( student talking time ) in a large classe: an essential tool for ELT classroom management - Tanzia, Sidddiqua (BRAC University, 2010)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2009.